The Historical Theme of the Years of Independence in Musical Theatre - Muzaffar Pirmatov (Researchparks Publishing, 2022)
This research paper points out that the historical theme of musical theatre and its role in the education of young people today are not comparable. It will also focus on our achievements in this field and the challenges that need to be addressed in the future. The significance of this theme is that the history of our statehood, our rich past and culture, the spirituality of our great ancestors are fully expressed through today's theatrical art.